The role for osmotic agents in children with acute encephalopathies: a systematic review - Mwai Leah; Gatakaa Hellen; Gwer Samson; Idro Richard; Newton Charles R (BMC, 2010)
Abstract Background Raised intracranial pressure (ICP) is known to complicate both traumatic and non-traumatic encephalopathies. It impairs cerebral perfusion and may cause death due to global ischaemia and intracranial herniation. Osmotic agents are widely used to control ICP. In children, guidelines for their use are mainly guided by adult studies. We conducted this review to determine the current evidence of the effectiveness of osmotic agents and their effect on resolution of coma and outcome in children with acute encephalopathy. Methods We searched several databases for published and unpublished studies in English and French languages, between January 1966 and March 2009. We considered studies on the use of osmotic agents in children aged between 0 and 16 years with acute encephalopathies. We examined reduction in intracranial pressure, time to resolution of coma, and occurrence of neurological sequelae and death. Results We identified four randomized controlled trials, three prospective studies, two retrospective studies and one case report. Hypertonic saline (HS) achieved greater reduction in intracranial pressure (ICP) compared to mannitol and other fluids; normal saline or ringer's lactate. This effect was sustained for longer when it was given as continuous infusion. Boluses of glycerol and mannitol achieved transient reduction in ICP. Oral glycerol was associated with lower mortality and neurological sequelae when compared to placebo in children with acute bacterial meningitis. HS was associated with lower mortality when compared to mannitol in children with non-traumatic encephalopathies. Conclusion HS appears to achieve a greater reduction in ICP than other osmotic agents. Oral glycerol seems to improve outcome among children with acute bacterial meningitis. A sustained reduction in ICP is desirable and could be achieved by modifying the modes and rates of administration of these osmotic agents, but these factors need further investigation.